ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN PADA SATUAN KERJA PELAKSANAAN JALAN NASIONAL WILAYAH IV PROVINSI NUSA TENGGARA TIMUR (NTT) - Suku, Maria Meilyantini Ero; Soleiman, Iriany Dewi; Ismail, Nuraini (Jurnal Riset Ilmu Akuntansi, 2020)
The purpose of this study was to determine the administrative factors and human resources, planning and documents of procurement of goods and services on budget absorption and also to find out the most dominant influences from administrative and human resource factors, which are found in the National Road Implementation Unit IV Region of NTT Province. . The study population consisted of 36 respondents who held positions in fields related to budget, including: PPK, PUMC, KTU, Technical Staff and Financial Staff (Reporting Officer) Satker, PPSPM, Treasurer, KTU, Planning Engineering Assistant, Supervision Engineering Assistant, in the Unit National Road Implementation Work Region IV NTT Province. The results of this study use multiple linear regression analysis which aims to determine whether or not there is an independent variable (X) on the dependent variable (Y). The analysis will be used with the help of the SPSS program. If analyzed, the t value of the planning document is 5.229 and t table is 2.03951, meaning that It can be seen that t is the planning document> t is the planning document table. Furthermore, it can also be seen that the t count of administrative records is 2.433> t table 2.03951, then it can be seen that the t count of HR competency is -0.987 <t table 2.03951, it is also seen that the t count of procurement documents is 0.345 <t table 2.03951, so it can be said that there are planning document variables and variables Administrative recording has a significant effect on budget absorption, while HR Competency Variables and Procurement Document Variables partially do not have an effect on budget absorption. The suggestion that can be given to the NTT Province National Road Implementation Unit IV in Ende is that the Institution / Ministry / Satker continues to pay attention to and optimize the absorption of the budget carried out every budget year through planning factors, administrative records, HR competence and procurement documents. From the four factors listed above, it is necessary to do so in order to determine their effect on the absorption of the budget, both partially and simultaneously on the absorption of the budget.